Kepemimpinan Kepala Sekolah dalam Mengembangkan Mutu Sumber Daya Guru di Kelompok Bermain (KB) Anggrek Landungsari Pekalongan Jawa Tengah - Aulia, Maulidiah Amirul; Asr Himsyah, Unun Zumairoh (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2022)
The school principal must have a strategy for the progress of his institution by developing the quality of teacher resources in the hope that each teacher will have good academic competence. All of the quality weaknesses of these educational components lead to the low academic quality of teachers. This study aims to find out how the principal's leadership in developing the quality of teacher resources is implemented in the Anggrek Landungsari Playgroup (KB) with a focus on the strategy, role and program of the Principal in Developing the Quality of Teacher Resources. This study uses a qualitative approach using a case study design. The results of the study found that the principal's strategy in developing the quality of teacher resources included upholding discipline, creating a conducive work climate, conducting supervision, and providing motivation. Programs carried out by school principals in developing the quality of teacher resources include forming training programs, assignments, further studies.